Strategi Kebertahanan Serta Keberlangsungan Usaha Batik Katura di Trusmi Kulon, Kecamatan Plered, Kabupaten Cirebon, Jawa Barat - Pusparani, Yori (KALBISCIENTIA Jurnal Sains dan Teknologi, 2019)
This study aims to examine the survival strategy and sustainability of the Katura batik business in Trusmi Kulon, Cirebon Regency. The increase in similar craft businesses and competition with modern textiles has made Trusmi batik entrepreneurs have to carry out strategies so that their business can survive. The concept of analysis of this study is based on observing the behavior and actions of rational and effective batik entrepreneurs in accordance with the social, political, economic and ecological environment in which they live. This research method uses qualitative research methods by compiling field data in the form of documentation and interviews with resource persons consisting of batik craftsmen. While data on the development of batik business in Trusmi itself was obtained by the literature approach method. The results of the study can be explained that the survival and sustainability of the Katura batik business is determined by internal factors, namely batik entrepreneurial behavior and external factors such as geographical conditions and market opportunities. The behavior of batik Trusmi entrepreneurs, shown by their tenacity, loyalty, hard work, and creativity, is one of the main factors that determine the success of a business. In addition, the survival and sustainability of batikbusiness is determined by the entrepreneurs in carrying out their business strategies.